2005
DOI: 10.1111/j.1365-3164.2005.00431.x
|View full text |Cite
|
Sign up to set email alerts
|

Hereditary equine regional dermal asthenia in three related Quarter horses in Brazil

Abstract: Hereditary equine regional dermal asthenia belongs to a group of inherited, congenital connective tissue dysplasias usually described as hyperelastosis cutis, cutaneous asthenia, dermatosparaxis, or Ehlers-Danlos-like syndrome. This report presents the clinical and histological features of three related Quarter horses affected with regional dermal asthenia. These horses had bilateral asymmetric lesions of the trunk and lumbar regions, where the skin was hyperextensible. Handling of the skin elicited a painful … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
26
0
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 16 publications
5
26
0
3
Order By: Relevance
“…The study also substantiates that horses with HERDA, even with frequent dermatological evaluations, may appear healthy for at least the first 1.5 years of life before showing severe clinical signs. As the disease has now been noted in South America 9 and Europe (B. Litschauer, personal communication, 2006) in addition to North America, it is increasingly important for the veterinary community to recognize the disease clinically and the limitations of a diagnosis via histopathology, particularly with regard to specimens from grossly normal skin.…”
Section: Discussionmentioning
confidence: 99%
“…The study also substantiates that horses with HERDA, even with frequent dermatological evaluations, may appear healthy for at least the first 1.5 years of life before showing severe clinical signs. As the disease has now been noted in South America 9 and Europe (B. Litschauer, personal communication, 2006) in addition to North America, it is increasingly important for the veterinary community to recognize the disease clinically and the limitations of a diagnosis via histopathology, particularly with regard to specimens from grossly normal skin.…”
Section: Discussionmentioning
confidence: 99%
“…First described as hyperelastosis cutis, hereditary equine regional dermal asthenia (HERDA) is an autosomal recessive disorder that is frequently observed in quarter horses (QHs) and their lineages . Hereditary equine regional dermal asthenia is clinically characterized by loose, hyperextensible and abnormally fragile skin, which is easily torn upon minor trauma, with seromas, haematomas, ulcers, scarring and tumour‐like masses developing primarily along the dorsum . A painful response may occur when the skin is manipulated …”
Section: Introductionmentioning
confidence: 99%
“…Thorough knowledge of the dermatological and morphological findings of HERDA‐affected horses and obtaining a definitive diagnosis are very important to minimize animal suffering and economic losses. However, only a few studies have reported the dermatological, morphological and molecular findings in QHs affected by HERDA worldwide . One study described the dermatological, morphological and ultrastructural findings in 50 HERDA‐affected horses and attempted to evaluate the accuracy of histopathological diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…Heterozygotes are not known to experience deleterious effects of the allele (Tryon et al 2009; Tryon et al 2007; Tryon et al 2005). HERDA has also been reported in Quarter Horses in Brazil (Borges et al 2005). …”
Section: Simple Genetic Diseases Of the Domestic Horsementioning
confidence: 82%